Stability of non-biofouling alginate/Zr.sup.IV coatings on Ti/TiO.sub.2 substrates - Jeong, Yeonwoo; Kim, Inho; Kang, Sung Min (Macromolecular research, 2024)
Surface modification with alginate (Alg) has attracted significant attention because of its potential applications in non-biofouling surface preparation, tissue engineering, and drug delivery. Much effort has been made to develop facile methods for preparing stable Alg coatings, including metal ion-mediated cross-link formation between polydopamine-coated solid surfaces and Alg. Although this approach has yielded Alg coatings that strongly inhibit platelet adhesion and fibrinogen adsorption on solid surfaces, their long-term stability, which is a prerequisite for practical applications, remains unknown. This study evaluated the long-term stability of Alg coatings under physiological conditions. The Alg coatings were incubated in phosphate-buffered saline at 37.5 °C for up to four weeks and subsequently analyzed for non-biofouling properties. The analysis revealed that the anti-protein adsorption and antiplatelet adhesion properties of the Alg coating were maintained at 80 and 90%, respectively, after four weeks of incubation. This study provides valuable insights into the long-term stability of Alg coatings and their potential for practical applications, addressing an overlooked crucial aspect. The findings contribute to advancements in tissue engineering, drug delivery systems, and other biomedical applications by enhancing our understanding of Alg coatings' durability and guiding the design of robust non-biofouling materials. Graphical abstract The long-term stability of alginate (Alg) coatings under physiological conditions is evaluated. Alg coatings are prepared using metal ion-mediated cross-link formation and subject to four weeks of incubation in phosphate-buffered saline at 37.5 °C. The Alg coatings maintain their antiprotein adsorption and antiplatelet adhesion properties at high percentages of up to 80% and 90%, respectively.